What is the destiny of information science doctors? - Pečarić, Đilda (Array, 2012)
This paper analyses professional orientation and activities of scientists that were awarded with a doctoral degree in information science at the University of Zagreb. We will give an overview of master theses and doctoral dissertations according to periods and disciplines of information science. The overview of scientific engagement of information science doctors in scientific and educational institutions and their promotions during scientific career is only a formal indicator of their contribution to information science and educational system. Bibliometric analyses and methods are used in order to: a) research their scientific activities according to scientific areas and scientific productions (analyses are done on the data obtained from CROSBI) ; b) indentify and show basic areas of their interest by co-word analysis (the results were visualized by key word clusters). The results obtained by this research produce quantitative indicators about the scientific productivity of information science doctors, their position and role in scientific and educational institutions, and give an overview of their scientific interests. These results are a presupposition for the evaluation of current development of scientific community in information science, but are also the basis for the prediction of their future development.